A STUDY OF THE DIMENSIONALITY OF THE SELECTION CRITERIA USED IN THE THAYER ACADEMY SUMMER SCIENCE PROGRAM. - Jones, Kenneth J. (Science Education, 1962)
The article examines the dimensionality of the selection criteria used in the Thayer Academy's summer science program in Braintree, Massachusetts. The program includes two weeks of classes followed by an eight week guided laboratory apprenticeship with a research scientist. The article presents the instruments used to select about one hundred students who are asked to come for an interview, including STEP Science, Cooperative Intermediate Algebra, the Otis Self Administering Test, high school science grades and high school math grades.